Comparative Assessment of Dietary Practices and Anthropometric Outcomes in school Students Consuming Mid-Day Meals Versus Home-Cooked Meals - Shazia Bahar, Muhammad Azhar Khan, Huma Tahir, Ramsha, Shehla Farhin, Muhammad Saqlain Raza, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Adequate childhood nutrition is essential for optimal growth and development. The type of meal consumed school-provided mid-day meals versus home-cooked food can significantly affect dietary adequacy and anthropometric outcomes. Objective: To compare dietary practices and anthropometric parameters among school students consuming mid-day meals and those consuming home-cooked meals. Methods: A comparative cross-sectional study was conducted at Khyber Teaching Hospital, Peshawar, and National Hospital and Medical Center, Lahore, from June 2022 to April 2023. A total of 100 students aged 6–14 years were enrolled and divided equally into two groups: mid-day meal consumers and home-cooked meal consumers. Data on dietary intake and food diversity were collected using structured questionnaires, while anthropometric measurements (height, weight, and BMI) were obtained following WHO guidelines. Statistical analysis was performed using SPSS version 26, applying independent t-tests and Chi-square tests, with p < 0.05 considered significant. Results: The mean BMI was 17.12 ± 2.46 kg/m² among mid-day meal consumers and 18.39 ± 2.81 kg/m² among home-meal consumers (p = 0.01). Stunting (18%) and underweight (22%) were more prevalent in the mid-day meal group, whereas overweight was more common in the home-meal group (15%). Dietary diversity scores were significantly higher in home-meal consumers (7.23 ± 0.98) compared to mid-day meal consumers (5.82 ± 1.07, p = 0.02). Conclusion: Students consuming home-cooked meals demonstrated superior dietary diversity and better anthropometric outcomes than those dependent on mid-day meals. Improving the nutritional quality and variety of mid-day meal programs is essential to promote balanced growth and prevent malnutrition among school children. Keywords: Mid-day meal, Home-cooked food, Dietary diversity, Anthropometry, BMI, Child nutrition, Pakistan